A 0.25-V fifth-order Butterworth low-pass filter based on fully differential difference transconductance amplifier architecture. (October 2019) - Pinto, Paulo M.; Ferreira, Luís H.C.; Colletta, Gustavo D.; Braga, Rodrigo A.S.
Abstract: This paper presents a fifth-order Butterworth low-pass filter based on the fully differential difference transconductance amplifier (FDDTA) building blocks. At first, the FDDTA has been stated and its operation has been evaluated. Then, a practical implementation using two fully differential inverter-based operational transconductance amplifiers (OTA) was investigated. This particular FDDTA implementation relies on two main features: the intrinsically matched transistors that assure similar transconductances and output conductances for both inverter-based OTA instances; and the inverter-based approach without internal nodes that reduces circuit complexity and power consumption since it requires no supplementary external calibration circuit such as tail current or bias voltage sources. Finally, the filter architecture, which consists of one inverter-based OTA input stage and five FDDTAs in a cascade connection has been evaluated, showing that it presents the expected fifth-order transfer function according to the Butterworth theory. The prototypes, implemented in a 130 nm CMOS process, operate in weak inversion supplied with 0.25 V and consumes 603 nW. Furthermore, they feature a DR of 57 dB in a 100 Hz bandwidth and a maximum THD of 54 dB, therefore, accomplishing specifications that suit for low-frequency applications.